Etching‐Free Epitaxial Growth of Gold on Silver Nanostructures for High Chemical Stability and Plasmonic Activity. (6th August 2015) - Liu, Hongpo; Liu, Tingzhuo; Zhang, Lei; Han, Lu; Gao, Chuanbo; Yin, Yadong
Abstract : A robust method for epitaxial deposition of Au onto the surface of Ag nanostructures is demonstrated, which allows effective conversion of Ag nanostructures of various morphologies into Ag@Au counterparts, with the anisotropic ones showing excellent plasmonic properties comparable to the original Ag nanostructures while significantly enhanced stability. Sulfite plays a determining role in the success of this epitaxial deposition as it strongly complexes with gold cations to completely prevent galvanic replacement while it also remains benign to the Ag surface to avoid any ligand‐assisted oxidative etching. By using Ag nanoplates as an example, it is shown that the corresponding Ag@Au nanoplates possess remarkable plasmonic properties that are virtually Ag‐like, in clear contrast to Ag@Au nanospheres that exhibit much lower plasmonic activities than their Ag counterparts. As a result, they display high durability and activities in surface‐enhanced Raman scattering applications. This strategy may represent a general platform for depositing a noble metal on less stable metal nanostructures, thus opening up new opportunities in rational design of functional metal nanomaterials for a broad range of applications. Abstract : Ag@Au core/shell nanostructures are synthesized by epitaxial growth of Au on Ag nanostructures, with the anisotropic ones such as nanoplates showing Ag‐like plasmonic properties and high stability. Sulfite plays a critical role in preventing galvanic replacement and oxidative etching of the Ag nanostructures. The resulting nanocrystals may find broad use in many plasmon‐based applications for superior activities and durability.